Comparison of Tibial Torsion Angles Between Elite Athletes and Sedentary People - Galip Bilen Kürklü; Ahmet Bayrak; Melda Pelin Yargıc; İsik Tuncer (Selcuk University, 2018)
Torsion is described as a rotational deformation where a long bone turns longitudinally around its own axe. Torsion in tibia is the main reason of children's stepping in-toe and out-toe. It not only creates orthopedic problems in the future, but also is a risk factor for lower extremity injuries. This study intends to compare Tibial Torsion Angle (TTA) of sedentary people to the soccer players of a Turkish Super Leage team. By comparing TTA angles of elite soccer players who train and compete regularly and have   high level of muscle power and endurance to the sedentary control group, it is aimed to determine whether high level soccer training effect TTA. The research was conducted between June-October 2015 on 25 elite soccer players and 25 sedantary people by measuring their right and left tibial torsion angles via transmalleolar measurement with a goniometer. Non-parametric tests were used in statistical analysis, Mann-Whitney U test was used for comparisons. There was not a significant difference in right-left measurements within groups. Between groups right TTA showed no significant difference but left TTA measurements varied significantly (p˂0.05). These findings suggest that tibial torsion angle differs according to physical activity level. It is understood that regular and long-time exercise programmes can change TTA.